The book of science and antiquities : a novel - Keneally, Thomas (Atria Books, 2019)
An award-winning documentary filmmaker, Shelby Apple is obsessed with reimagining the full story of the Learned Man<U+2014>a prehistoric man whose remains are believed to be the link between Africa and ancient Australia. From Vietnam to northern Africa and the Australian Outback, Shelby searches for understanding of this enigmatic man from the ancient past, unaware that the two men share a great deal in common. Some 40,000 years in the past, the Learned Man has made his home alongside other members of his tribe. Complex and deeply introspective, he reveres tradition, loyalty, and respect for his ancestors. Willing to sacrifice himself for the greater good, the Learned Man cannot conceive that a man millennia later could relate to him in heart and feeling.